Genetic instability of a single exposure to sevoflurane at different concentrations in monitored mice - Destro, Maria Vitória [UNESP]; Silva, Mariane A. P. [UNESP]; Grassi, Tony Fernando [UNESP]; de Carvalho, Lídia R. [UNESP]; Salvadori, Daisy M. F. [UNESP]; Braz, Leandro Gobbo [UNESP]; Braz, Mariana Gobbo [UNESP] (Wiley, 2025)
Sevoflurane is an inhalation anesthetic widely used for general anesthesia, but its genotoxic potential is controversial in clinical studies. It is unknown whether the effects are due to surgery or the anesthetic. Thus, for the first time, the present study investigated genotoxicity in peripheral blood cells and in target organs (liver, lung, and kidney) and micronucleus (MN) in the bone marrow of a single exposure to sevoflurane at three different concentrations in monitored mice. Ninety Swiss mice were distributed into the following groups: exposure to sevoflurane at 3.3% (low), 4.5% (intermediate), and 6.0% (high) in 40% oxygen (O2) for 2 h; negative control (no exposure); negative control with O2; and positive control. The exposed animals were heated, monitored for vital signs (temperature, O2 saturation, heart rate/pulse, and respiratory rate), and anesthetized via a modern low-flow digital system. Mice were euthanized 2 and 24 h after exposure for evaluation by the comet assay and MN test, respectively. No DNA damage occurred in the 3.3% group for any of the organs evaluated, and no genotoxic or mutagenic effects were observed at any sevoflurane concentration in the peripheral blood or liver cells. However, a significant increase in DNA damage was observed at higher concentrations in kidney (4.5%) and lung cells (6.0%) and in the MN frequency (groups 4.5% and 6.0%). No cytotoxicity or histological alterations were observed. In conclusion, high concentrations of sevoflurane induce DNA damage, but concentrations equivalent to those used in clinical practice do not demonstrate genotoxic or mutagenic effects.
Keywords: comet assay; general anesthetic; micronucleus test